Information society with Chinese characteristics. Discursive evolution of the neo-industrialisation strategy in the people’s daily. - Hong, Yu (Javnost-The Public, 2008)
By focusing on the Chinese offi cial discourse of “neoindustrialisation” published on the People’s Daily, this article not only provides an understanding of the Chinese offi cial understanding of information society and information economy, but also foregrounds the issue of information in China’s confl icted reintegration with global capitalism. This article argues that, deviant from the Western discourse of post-industrialism, the neo-industrialisation strategy promotes a coordinated effort to both “industrialise” and “informationise” the economy. Moreover, pragmatic concerns with China’s realities, including unfi nished industrialisation, structural unemployment and the domestic demands for all-around national development, all fi nd echoes in the discourse of neo-industrialisation. By providing a politicaleconomic contextualisation of this discourse, this article also strives to provide an insight of the most recent plan of forming a “super” Ministry of Industry and Information Technology in the Chinese government, which was announced in March 2008.